Phyllosticta citricarpa: diversidade genética temporal em pomares de citrus sinensis e sensibilidade a fungicidas - Souza, Andressa de [UNESP] (2015)
Citrus Black Spot (CBS), caused by the fungus Phyllosticta citricarpa, is spread over continents in the world. Its symptoms cause fruit depreciation and those severely infected fall prematurely. Given the economic importance of this disease, we carried out analysis of the genetic structure of two P. citricarpa isolates collections, obtained from a single citrus farm in a seven years interval. Fruits were collected from Pera and Valencia orange varieties in 2005 and 2012. The isolates obtained were identified by sequences analysis of ITS region and GPDH and TEF1 genes. Thus, 80 and 115 isolates of the 2005 and 2012 collections, respectively, were identified as P. citricarpa. Among the 2012 collection only six Phyllosticta capitalensis isolates were found. Higher amount of sequences containing genetic variations were identified in the isolates from the last fruits sampling, especially in populations derived from Valencia oranges. By applying AFLP markers it was evidenced genetic differentiation among P. citricarpa populations from Valencia oranges obtained between 2005 and 2012, whose predominant genotype in 2012 was that found in Pera populations from both periods. Through analysis of genetic relationship among isolates, it was assumed that individuals with favored genotypes have first appeared among P. citricarpa populations of Pera plants, and further migrated to Valencia orchards. Genetic populations uniformity over the seven years and low polymorphism observed among them, over generations, are indicative of low genetic recombination between individuals. Sequences of polymorphic bands between isolates of 2005 and 2012 Valencia collections presented similarity with those of ABC transporters Family proteins, which act as efflux pumps of cytotoxic compounds, as fungicides, and to NADH dehydrogenase proteins. Such gene modifications might be responsible for variability of sensibility responses of the isolates to strobilurins, which ...